Analysis of myositis autoantibodies in Chinese patients with cancer‐associated myositis. Issue 8 (27th March 2020) - Li, Liubing; Liu, Chenxi; Wang, Qian; Wu, Chanyuan; Zhang, Yanfang; Cheng, Linlin; Wen, Xiaoting; Zeng, Xiaofeng; Zhang, Fengchun; Li, Yongzhe
Abstract: Background: Cancer‐associated myositis (CAM) has poor prognosis and causes higher mortality. In general, myositis‐specific autoantibodies (MSAs) and myositis‐associated autoantibodies (MAAs) have been shown to be useful biomarkers for its diagnosis. Methods: In the present study, focus was given in assessing the presence, prevalence, and diagnostic values of myositis autoantibodies in Chinese patients diagnosed with CAM. The sera collected from 49 CAM patients, 108 dermatomyositis/polymyositis (DM/PM) patients without cancer, 105 disease controls, and 60 healthy controls were detected for the presence of 16 autoantigens (Jo‐1, OJ, EJ, PL‐7, PL‐12, MDA5, TIF1γ, Mi‐2α, Mi‐2β, SAE1, NXP2, SRP, Ku, PM‐Scl75, PM‐Scl100, and Ro‐52) using a commercial Euroline assay. Results: The frequency of anti‐TIF1γ was significantly higher in CAM patients than in DM/PM patients without cancer (46.9% vs 14.8%, P  < .001). Importantly, the sensitivity and specificity for this MSA were 46.9% and 85.2%, respectively. These helped to differentiate CAM patients from DM/PM patients without cancer. However, there was no difference in other MSAs and MAAs between CAM and DM/PM patients without cancer. Conclusion: The present study indicates that anti‐TIF1γ levels can serve as important biomarkers for CAM diagnosis and help in distinguishing between CAM and DM/PM patients without cancer.